The simplified expression of (-11/2x+30)-2(-11/4x-5/2) is 35
<h3>How to simplify the expression?</h3>
The expression is given as:
(-11/2x+30)-2(-11/4x-5/2)
Expand the bracket
-11/2x + 30 + 11/2x + 5
Collect the like terms
11/2x -11/2x + 30 + 5
Evaluate the like terms
35
Hence, the simplified expression of (-11/2x+30)-2(-11/4x-5/2) is 35
Read more about expressions at:
brainly.com/question/723406
#SPJ1
B. 1/40…. You divide 1/2 by 20 to find out how much hand sanitizer was used on each desk. You can keep change flip meaning keep the 1/2 change the division to multiplication and flip the 20 to 1/20 then multiply. 1/2 by 1/20 which equals 1/40.
Answer:
-5
Step-by-step explanation:
2x+3=-7
2x=-7-3
2x=-10
x=-10/2
x=-5
Answer:
Wayne west would have $5,015 in six months
Step-by-step explanation:
The formula for exponential regression model is y = αβˣ
Where y is amount of money in 1000 dollars
x is time in months
We are given that α = 4.2 and β = 1.03 and x = 6 months
Therefore, based on this model, y = αβˣ, the amount he would have in 6 months, y = ![4.2*(1.03) ^{6}](https://tex.z-dn.net/?f=4.2%2A%281.03%29%20%5E%7B6%7D)
y = 5.015 × 1000 = $ 5,015